1990
DOI: 10.1128/mcb.10.2.770
|View full text |Cite
|
Sign up to set email alerts
|

Phosphotyrosine-containing lactate dehydrogenase is restricted to the nuclei of PC12 pheochromocytoma cells.

Abstract: There are five lactate dehydrogenase (LDH) isoenzymes, composed of various combinations of two types of subunits. LDH-5, which contains only the LDH A subunit, is known to be present in both the cytoplasm and the nucleus, to act as a single-stranded DNA-binding protein possibly functioning in transcription and/or replication, and to undergo phosphorylation of tyrosine 238 in approximately 1% of the enzyme after cell transformation by certain tumor viruses. We have characterized LDH from wild-type PC12 pheochro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
1
1

Year Published

1992
1992
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 29 publications
1
25
1
1
Order By: Relevance
“…However, further mass spectrometry-based studies revealed that rFGFR1 directly phosphorylates purified, recombinant LDH-A at Y10 and Y83 in an in vitro kinase assay, but not at Y172 and Y239 as predicted. FGFR1 may activate alternative tyrosine kinases in cells which subsequently phosphorylate LDH-A at Y172 and Y239; phosphorylation of LDH-A Y239 was previously implied to correlate with LDH-A nuclear localization in cancer cells (32). Mouse LDH-A harbors V10 instead of Y10, which explains why we could not detect Y10 phosphorylation in murine hematopoietic Ba/F3 cells expressing ZNF198-FGFR1 in the phosphoproteomics studies.…”
Section: Resultscontrasting
confidence: 51%
“…However, further mass spectrometry-based studies revealed that rFGFR1 directly phosphorylates purified, recombinant LDH-A at Y10 and Y83 in an in vitro kinase assay, but not at Y172 and Y239 as predicted. FGFR1 may activate alternative tyrosine kinases in cells which subsequently phosphorylate LDH-A at Y172 and Y239; phosphorylation of LDH-A Y239 was previously implied to correlate with LDH-A nuclear localization in cancer cells (32). Mouse LDH-A harbors V10 instead of Y10, which explains why we could not detect Y10 phosphorylation in murine hematopoietic Ba/F3 cells expressing ZNF198-FGFR1 in the phosphoproteomics studies.…”
Section: Resultscontrasting
confidence: 51%
“…Several recent reports suggest that tyrosine phosphorylation might regulate the function of some nuclear proteins. cdc2, lactose dehydrogenase, or androgen receptor are examples of nuclear proteins whose function or subcellular localization is affected by tyrosine phosphorylation (37)(38)(39). Furthermore, two other proteintyrosine kinases, the c-Abl IV protein and the FER gene product, have also been localized to the cell nucleus (40,41).…”
Section: Discussionmentioning
confidence: 99%
“…Several isoforms of hexokinase play a key role in mitochondrion-mediated apoptosis by modulating proapoptotic molecules including Bax and Bad, suggesting that the glycolytic pathway and apoptosis are integrated (9,15,33). The roles of LDHA and GAPD proteins in glycolysis are well-established, yet the nuclear localization of these proteins suggest additional biological functions (45). Recently, GAPD and LDH were both found in a transcriptional coactivator complex that assists the Oct-1 transcription factor in regulating histone H2B expression (44).…”
Section: Discussionmentioning
confidence: 99%